2016
DOI: 10.1111/ibi.12366
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Afro‐Palaearctic passerine migrants in western Europe and the impacts of seasonal weather variables

Abstract: Populations of migratory songbirds in western Europe show considerable variation in population trends between species and regions. The demographic and environmental causes of these large-scale patterns are poorly understood. Using data from Constant Effort mist-netting studies, we investigated relationships between changes in abundance, adult survival and seasonal weather conditions among 35 western European populations of eight species of migratory warblers (Sylviidae). We used cross-species and withinspecies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 105 publications
(240 reference statements)
4
52
0
Order By: Relevance
“…As a result, Reed Warblers are very sensitive to the prevailing environmental conditions at important stopover sites. Our results are in line with those reported in numerous earlier studies of various avian species that provide evidence for relationships between survival and/or population levels and indices of wet season rainfall at wintering areas (Peach et al 1991;Baillie and Peach 1992;Schaub et al 2005, García-Pérez et al 2014Ockendon et al 2014;Johnston et al 2016) or along migratory routes (LaManna et al 2012). However, we did not find a similar relationship between survival and precipitation for spring stopover sites or wintering areas.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As a result, Reed Warblers are very sensitive to the prevailing environmental conditions at important stopover sites. Our results are in line with those reported in numerous earlier studies of various avian species that provide evidence for relationships between survival and/or population levels and indices of wet season rainfall at wintering areas (Peach et al 1991;Baillie and Peach 1992;Schaub et al 2005, García-Pérez et al 2014Ockendon et al 2014;Johnston et al 2016) or along migratory routes (LaManna et al 2012). However, we did not find a similar relationship between survival and precipitation for spring stopover sites or wintering areas.…”
Section: Discussionsupporting
confidence: 92%
“…Ockendon et al (2014) also did not find a positive correlation between rainy season rainfall and mean winter NDVI for the humid zone, where Reed Warblers from central Europe (but also, for example, Willow and Garden Warblers, House Martins and Spotted Flycatchers) winter and fuel up before their spring migration (the authors did find positive correlations for the arid zone and southern Africa). Variable sensitivity of different habitats to rainfall levels may explain the inconsistent relationships between survival and rainfall in Africa that were found for different bird species (Boano et al 2004;Salewski et al 2013;Ockendon et al 2014;Johnston et al 2016). Our results are also in line with the earlier findings of Thaxter et al (2006) and Zwarts et al (2009), who did not find a significant effect of African droughts on the size of Reed Warbler populations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Strong regional covariation in annual adult survival rates throughout the period of population declines was apparent (figure 1 a ) suggesting that adult survival rates are influenced by environmental factors operating over large spatial scales, across breeding, passage and/or wintering grounds. Previous studies have linked changes in migrant demography to rainfall in the Sahel [18,19,41] and changes in conditions in similar population bottlenecks, such as the Iberian peninsula, could impact over-wintering and passage conditions for birds from breeding ranges throughout Europe. However, conservation actions designed to influence such large-scale drivers of adult survival rates are likely to be, at best, extremely difficult to design and implement.…”
Section: Discussionmentioning
confidence: 99%
“…With low temperatures, nonhibernating endotherms are confronted with increasing energy requirements to enhance thermogenesis while food is a scarce resource (Boos et al 2007, Deville et al 2014. In many bird species it has thus been shown that winter conditions such as low temperatures or consecutive frosts influence survival (e.g., Deville et al 2014, Johnston et al 2016. In France, a negative relationship between winter temperature and woodcock survival was also found, as well as escape behavior below a certain temperature threshold (Tavecchia et al 2002, Péron et al 2011a, presumably because dealing with such conditions would be riskier than moving away from their usual wintering areas (Duriez 2003).…”
Section: Winter Survival Ratementioning
confidence: 99%